The World of the New Testament Cultural, Social, and Historical Contexts - Green, Joel B. 1956-; McDonald, Lee Martin 1942- (Grand Rapids Baker Academic, 2013)
A team of distinguished specialists introduces the Jewish, Hellenistic, and Roman backgrounds necessary for understanding the New Testament and the early church
Intro -- Contents -- Illustrations -- Contributors -- Abbreviations -- Introduction -- New Testament Chronology -- Exile -- The Hasmoneans and the Hasmonean Era -- The Herodian Dynasty -- Monotheism -- The Scriptures and Scriptural Interpretation -- Greek Religion -- The Imperial Cult -- Greco-Roman Philosophical Schools -- Civic and Voluntary Associations in the Greco-Roman World -- Economics, Taxes, and Tithes -- Slaves and Slavery in the Roman World -- Women, Children, and Families in the Greco-Roman World -- Education in the Greco-Roman World -- The Jewish People in the Context of Roman Hellenism -- Temple and Priesthood -- Jews and Samaritans -- Pharisees, Sadducees, and Essenes -- The Dead Sea Scrolls -- Prophetic Movements and Zealots -- Apocalypticism -- Synagogue and Sanhedrin -- Jews in the Diaspora -- Noncanonical Jewish Writings -- Jewish Identity, Beliefs, and Practices -- Jewish Education -- Healing and Healthcare -- The Literary Context of Early Christianity -- Reading, Writing, and Manuscripts -- Pseudonymous Writings and the New Testament -- Literary Forms in the New Testament -- Homer and the New Testament -- Josephus and the New Testament -- Philo and the New Testament -- Rabbinic Literature and the New Testament -- Early Noncanonical Christian Writings -- The Geographical Context of the New Testament -- Jesus Research and Archaeology -- Egypt -- Palestine -- Syria, Cilicia, and Cyprus -- The Province and Cities of Asia -- Galatia -- Macedonia -- Achaia -- Rome and Its Provinces -- Additional Resources -- Money in the New Testament Era -- Measurements in the New Testament Era -- Glossary -- Index of Ancient Sources -- Index of Biblical Texts -- Index of Modern Authors -- Index of Subjects
Keywords: Bible. -- New Testament -- Criticism, interpretation, etc; Bible. -- New Testament -- History of Biblical events; Church history -- Primitive and early church, ca. 30-600; Civilization, Greco-Roman -- Social aspects; Jews -- History -- 586 B.C.-70 A.D; Jews -- Palestine -- Social life and customs -- To 70 A.D; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D